Data quality at the Bulgarian National Cancer Registry: An overview of comparability, completeness, validity and timeliness. Issue 3 (June 2015) - Dimitrova, Nadya; Parkin, Donald Maxwell
Highlights: We evaluated the data quality at the Bulgarian National Cancer Registry (BNCR). We estimated comparability, completeness, validity and timeliness of the most recent cancer data. BNCR yields comparable data that are close-to-complete, timely and reasonably accurate. This is a prerequisite for BNCR to expand its role to more areas of cancer control. Abstract: Reporting of neoplasms in Bulgaria has been compulsory since a directive from the Ministry of Health in 1951. The quality of cancer registry data has been estimated rather infrequently in past years. We aimed to provide a comprehensive evaluation of the quality of the data at the Bulgarian National Cancer Registry (BNCR). Quantitative and semi-quantitative methods were applied for cancers diagnosed during the whole period 1993–2010, and also for cases diagnosed in 2006–2010. The methods used include historic data methods, mortality-to-incidence ratios (M:I), capture–recapture and death-certificate methods, proportions of morphologically verified cases (MV%), death-certificate-only cases (DCO%), and cases with missing information (primary site unknown, PSU%; stage unknown, SU%). The BNCR coding and classification systems follow international standards. The overall completeness was estimated at 92.6–94.7% for the period 2006–2010, with variations between cancer sites (86.7–98.5%). During the period 1993–2010, M:I decreased to 0.5 for males and 0.4 for females, MV increased to 87.4%, DCO and SU decreased to 4.8% and 18.8%, respectively, and PSU remained at the same level of about 4% for both sexes together. Sub-analysis revealed differences by site, sex and age groups. The comparison with other registries from the region showed similar incidence rates and directions of trends: M:I, MV% and DCO% that were not significantly different. The underreporting in 2008 and 2009 due to timely publication was estimated at an overall 0.8% and 0.5%, respectively. The present review showed that the BNCR yields internationally comparable data that are reasonably accurate, timely, and close to complete, especially in recent years. This is a prerequisite for the BNCR to expand its role to more areas of cancer control.